VEGF inhibition alters neurotrophin signalling pathways and induces caspase‐3 activation and autophagy in rabbit retina. Issue 10 (19th March 2019) - Segatto, Marco; Fico, Elena; Gharbiya, Magda; Rosso, Pamela; Carito, Valentina; Tirassa, Paola; Plateroti, Rocco; Lambiase, Alessandro
Abstract: This study sought to evaluate the prospective role exerted by vascular endothelial growth factor (VEGF) in the modulation of nerve growth factor (NGF) and brain‐derived neurotrophic factor (BDNF) signalling pathways in the rabbit retina. To reach this aim, the anti‐VEGF agents aflibercept and ranibizumab were used as a pharmacological approach to evaluate the putative consequences elicited by VEGF inhibition on neurotrophin signalling. VEGF inhibition determined a marked imbalance in proneurotrophin expression, a significant reduction in TrkA and TrkB phosphorylation states and a decrease in the pan‐neurotrophin receptor p75. Importantly, VEGF blockade also caused a strong increase in cleaved caspase‐3, beclin‐1 and lipidated LC3. The effects were more pronounced in the aflibercept group when compared with ranibizumab‐treated rabbits, particularly 1 week after injection. This study demonstrates that VEGF exerts pivotal physiological roles in regulating NGF and BDNF pathways in the retina, as its inhibition by anti‐VEGF agents deeply impacts neurotrophin homeostasis. These events are accompanied by a sustained induction of apoptotic and autophagic markers, suggesting that anti‐VEGF‐dependent impairments in neurotrophin signalling could be responsible for the activation of retinal cell death pathways. Abstract : Here, we aimed at evaluating the putative role exerted by vascular endothelial growth factor (VEGF) in the modulation of neurotrophin signalling pathways in the rabbit retina. VEGF blockade by ranibizumab and aflibercept deeply alters nerve growth factor (NGF) and brain‐derived neurotrophic factor (BDNF) signalling, and concurrently increases the expression of apoptotic and autophagic markers. VEGF activity is essential for the maintenance of trophic support mediated by neurotrophins in retinal cells.